Air pollution and rhinitis - Rosario, Cristine Secco; Urrutia-Pereira, Marilyn; Murrieta-Aguttes, Margarita; D’Amato, Gennaro; Chong-Silva, Debora Carla; Godoi, Ricardo Henrique Moreton; Rosario Filho, Nelson A. (Frontiers in Allergy, 2024)
Rhinitis arises from either allergic or non-allergic inflammation of the nasal mucosa, characterized by the infiltration of inflammatory cells into the tissue and nasal secretions, along with structural alterations in the nasal mucosa. The pathways through which air pollution affects rhinitis may diverge from those affecting asthma. This article aims to review the effects of diverse air pollutants on the nose, the correlation of climate change and pollution, and how they aggravate the symptoms of patients with rhinitis.